2024
DOI: 10.18176/jiaci.0961
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Successful Desensitization to Ivacaftor and Elexacaftor/Tezacaftor/Ivacaftor in a Delayed Hypersensitivity Reaction Confirmed by the Lymphocyte Transformation Test

P Mir-Ihara,
L De Las Vecillas,
R Heredia
et al.

Abstract: cystic fibrosis transmembrane conductance modulators (CFTR); cystic fibrosis (CF); forced expiratory volume in the first second (FEV1); elexacaftor/tezacaftor/ivacaftor (ETI); Ivacaftor (IVA); lymphocyte transformation test (LTT); stimulation index (SI) PATIENT´S CONSENTWritten patient consent has been obtained for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…One patient had positive patch tests to ELX/TEZ/IVA and IVA, confirming a type IV hypersensitivity, which aligns with findings reported by Balijepally et al, 2022 . Recently, Mir-Ihara et al, 2023 have reported a case where a man presented a maculopapular rash and eosinophilia seven days into treatment with ELX/TEZ/IVA and underwent epicutaneous patch tests with ELX/TEZ/IVA and IVA in 30% petrolatum, showing negative readings at 48, 72, and 96 h.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had positive patch tests to ELX/TEZ/IVA and IVA, confirming a type IV hypersensitivity, which aligns with findings reported by Balijepally et al, 2022 . Recently, Mir-Ihara et al, 2023 have reported a case where a man presented a maculopapular rash and eosinophilia seven days into treatment with ELX/TEZ/IVA and underwent epicutaneous patch tests with ELX/TEZ/IVA and IVA in 30% petrolatum, showing negative readings at 48, 72, and 96 h.…”
Section: Discussionmentioning
confidence: 99%